AB0816 Comprehensive analysis of a new chemical compound for the treatment of osteoarthritis by a proteomic approach in human chondrocytes. (15th June 2017) - Cheleschi, S; Calamia, V; Fernandez-Moreno, M; Palma, A De; Galeazzi, M; Anzini, M; Fioravanti, A; Blanco, FJ
Abstract : Background: Selective cyclooxigenase (COX)-2 inhibitors were developed to prevent NSAIDs gastro-intestinal adverse effects. VA692, a new hydroxyetyl selective COX-2 inhibitor, showed anti-inflammatory, anti-nociceptive and chondroprotective properties. Proteomics is being applied for the study of drug mode of action, toxicity and to identify new drugs targets. Objectives: The aim of this study was to analyze the anti-inflammatory effect of VA692, in comparison with celecoxib. By iTRAQ methodology, we quantitatively analyzed the different expressed profiles in T/C-28a2 cell line treated with the studied drugs in presence of IL-1β. Methods: Human T/C-28a2 chondrocytes cell line were generated by Goldring group. Human articular cartilage was obtained from femoral heads of five OA patients. Cells were incubated with VA692 and celecoxib (1, 0.5 and 0.2μM) in presence of Interleukin (IL)-1β (5ng/ml) for 48h. The expression of inflammatory cytokines and anti-oxidant enzymes was evaluated by quantitative qRT-PCR, PGE2 release by ELISA, and apoptosis and ROS production by flow cytometry. T/C-28a2 cell line was also processed to carry out western blot tests and finally employed for the iTRAQ analysis. Statistical analysis was performed by ANOVA and Bonferroni multiple comparison tests. Results: IL-1β-stimulated chondrocytes showed a significant increase (p<0.001) of COX-2, IL-1β, IL-6, IL-8, superoxide dismutase (SOD)-2 and catalase (CAT) gene expression, as well as of PGE2 levels. The tested drugs significantly counteracted the effect of IL-1β, with a better modulation by VA692 1μM in T/C-28a2 cell line (p<0.01 for COX-2, IL-1β, IL-8, CAT; p<0.001 for IL-6, SOD-2). Regarding apoptosis and ROS production, the new drug was able to significantly reduce (p<0.05) their increase induced by IL-1β (p<0.05). Proteomic analysis led to identification of 797 proteins in T/C28a2 cell line, 123 of which were significantly modulated by VA692 in presence of IL-1β (p<0.001), and 34 by IL-1β alone (p<0.05). 22 proteins were commonly modulated in both groups, thus indicating that 101 proteins were regulated by VA692 in a specific manner. Among the proteins down-regulated by VA692, some with structural function were detected, responsible for cytoskeleton riorganization, as well as chaperones (heat shock proteins) and glycolitic enzymes. Proteins involved in calcium metabolism and in ribosome biogenesis resulted up-regulated instead, as well as SOD-2 as confirmed by western blot analysis. Conclusions: Our data demonstrated the anti-inflammatory effect of VA692, suggesting also its anti-apoptotic and anti-oxidant role. The proteomic profile showed that VA692 induced not only an anti-inflammatory effect in chondrocytes but, interestingly, this compound also seemed to regulate their anabolic response. References: Hochberg MC et al.Arthritis Care Res 2012. McAlindon TE et al. Osteoarthritis Cartilage 2014. Bingham CO III. Cleve Clin J Med 2002. Anzini M et al. J Med Chem 2013. Calamia V et al.Arthritis Res Ther 2010. Disclosure of Interest: None declared